2018
DOI: 10.1111/bjh.15174
|View full text |Cite
|
Sign up to set email alerts
|

In chronic lymphocytic leukaemia with complex karyotype, major structural abnormalities identify a subset of patients with inferior outcome and distinct biological characteristics

Abstract: Complex karyotype (CK) is a negative prognostic factor in chronic lymphocytic leukaemia (CLL). However, CK is a heterogeneous cytogenetic category. Unbalanced rearrangements were present in 73·3% of 90 CLL patients with CK (i.e. ≥3 chromosome aberrations in the same clone), and were associated with a shorter overall survival (P = 0·025) and a shorter time to first treatment (P = 0·043) by multivariate analysis. Patients with unbalanced rearrangements presented a distinct mRNA expression profile. In conclusion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 15 publications
2
33
0
Order By: Relevance
“…None of the patients with a complex karyotype (≥ 3) as well as del(11q) and del(17p) attained a CR after chemotherapy. In CLL, the prognostic significance of a complex karyotype had also been reported in other recent studies [23][24][25].…”
Section: Discussionsupporting
confidence: 68%
“…None of the patients with a complex karyotype (≥ 3) as well as del(11q) and del(17p) attained a CR after chemotherapy. In CLL, the prognostic significance of a complex karyotype had also been reported in other recent studies [23][24][25].…”
Section: Discussionsupporting
confidence: 68%
“…Similar to other haematological malignancies, the earliest prognostic abnormalities detected were cytogenetic: del(17p)/del(11q) and del(13q) were associated with shorter and longer OS rates respectively [121]. More recently, a complex karyotype (defined as ≥ 3 cytogenetic abnormalities in a single clone) has been shown to be associated with a poor prognosis with those patients with unbalanced chromosomal rearrangements having the worst prognosis [122]. However, technical difficulties with the culture of CLL cells means failure rates for conventional karyotyping are high and alternative technologies such as WGS may be required.…”
Section: Chronic Lymphocytic Leukaemiamentioning
confidence: 78%
“…Recently, Rigolin et al , showed that within patients carrying CK as defined by the presence of 3 or more aberrations, the presence of unbalanced translocations (i.e. chromosome additions, derivatives, insertions, duplications, ring-, dicentric- and marker-chromosomes) was associated with a worse outcome in terms of OS and TTFT (HR 2.773; 95% CI, 1.056-7.281; P=0.038 and HR 2.375; 95% CI, 1.027-5.492; P=0.043) [ 97 ]. Interestingly, a distinct mRNA expression profile, with a deregulation of genes involved in cell cycle control and DNA damage response, was documented in patients with a CK carrying unbalanced rearrangements [ 97 ].…”
Section: Resultsmentioning
confidence: 99%